Insights into the mechanisms of triptolide nephrotoxicity through network pharmacology-based analysis and RNA-seq - Luo, Yue-Ming; Yang, Shu-Dong; Wen, Miao-Yu; Wang, Bing; Liu, Jia-Hui; Li, Si-Ting; Li, Yu-Yan; Cheng, Hong; Zhao, Li-Li; Li, Shun-Min; Jiang, Jian-Jun (Frontiers in Plant Science, 2023)
Introduction Triptolide (TPL) is a promising plant-derived compound for clinical therapy of multiple human diseases; however, its application was limited considering its toxicity. Methods To explore the underlying molecular mechanism of TPL nephrotoxicity, a network pharmacology based approach was utilized to predict candidate targets related with TPL toxicity, followed by deep RNA-seq analysis to characterize the features of three transcriptional elements include protein coding genes (PCGs), long noncoding RNAs (lncRNAs) and circular RNAs (circRNAs) as well as their associations with nephrotoxicity in rats with TPL treatment. Results & Discussion Although the deeper mechanisms of TPL nephrotoxcity remain further exploration, our results suggested that c-Jun is a potential target of TPL and Per1 related circadian rhythm signaling is involved in TPL induced renal toxicity.